2021
DOI: 10.1038/s41598-021-93702-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV envelope antigen valency on peptide nanofibers modulates antibody magnitude and binding breadth

Abstract: A major challenge in developing an effective vaccine against HIV-1 is the genetic diversity of its viral envelope. Because of the broad range of sequences exhibited by HIV-1 strains, protective antibodies must be able to bind and neutralize a widely mutated viral envelope protein. No vaccine has yet been designed which induces broadly neutralizing or protective immune responses against HIV in humans. Nanomaterial-based vaccines have shown the ability to generate antibody and cellular immune responses of increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…This observation suggests an enhanced binding capacity induced by gp120-Q11 vaccination as compared to soluble gp120. Consistent with previous findings in mice ( 33 ), these results reinforce the importance of valency in enhancing antibody binding responses to HIV glycoprotein antigens.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This observation suggests an enhanced binding capacity induced by gp120-Q11 vaccination as compared to soluble gp120. Consistent with previous findings in mice ( 33 ), these results reinforce the importance of valency in enhancing antibody binding responses to HIV glycoprotein antigens.…”
Section: Resultssupporting
confidence: 92%
“…In a recent study, we demonstrated that conjugating the HIV gp120 antigen to Q11 nanofibers induced antibody responses with stronger binding to heterologous HIV Envelope (Env) antigens than soluble gp120 in immunized mice and that enhancement of the antibody response was driven by the multivalent presentation of gp120 ( 33 ). Here, we immunized rabbits with Q11-conjugated gp120 (gp120-Q11) to evaluate the functional profile of vaccine-elicited antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to subcutaneously delivered NFs, more resident T cells were produced providing faster response to influenza infection. Chemical plasticity enables customized display of antigens of self-assembling NFs, as demonstrated in the model HIV vaccine where folded glycoprotein antigen valency was associated with increased magnitude and breadth of immune response [ 151 ].…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…Genetiс nаnо vассines have also played an influential role in the treatment of Ebola, HIV-1, аnd оrаl infeсtiоns [55,56]. DNA аnd RNA vассines are preferred to traditional vaccines owing to their simple purification and low production cost, however, their targeted delivery faces some constraints due to their specificity and stability [14,[57][58][59][60].…”
Section: Nаnоzymes In Vассine рRоduсtiоn аNd Immunizаtiоnmentioning
confidence: 99%